Investigation of Important Odorants of Palm wine (Elaeis guineensis). - Lasekan, Olusegun; Büttner, Andrea; Christlbauer, Monika (Food Chemistry, 2007)
Palm wine (Elaeis guineensis) was sensorially evaluated and the key odorants were investigated by means of high resolution gas chromatography–olfactometry and mass spectrometry of solvent extracts as well as headspace samples. A total of 41 compounds were identified, 32 of them previously unknown in palm wine. From these, a total of 13 compounds were quantified by means of stable isotope dilution assays. Quantitation and calculation of the odour-activity values (OAVs) of the 13 key odorants revealed that the earthy-smelling 3-isobutyl-2-methoxypyrazine, the buttery-smelling acetoin, the fruity compounds ethyl hexanoate, 3-methylbutyl acetate and the popcorn-like-smelling 2-acetyl-1-pyrroline are likely to be important odorants of palm wine, with 3-isobutyl-2-methoxypyrazine, acetoin, and 2-acetyl-1-pyrroline being reported here for the first time as aroma constituents of palm wine.<br